2021
DOI: 10.1002/1873-3468.14206
|View full text |Cite
|
Sign up to set email alerts
|

Cardiolipin prevents pore formation in phosphatidylglycerol bacterial membrane models

Abstract: Several antimicrobial peptides, including magainin and the human cathelicidin LL‐37, act by forming pores in bacterial membranes. Bacteria such as Staphylococcus aureus modify their membrane's cardiolipin composition to resist such types of perturbations that compromise their membrane stability. Here, we used molecular dynamic simulations to quantify the role of cardiolipin on the formation of pores in simple bacterial‐like membrane models composed of phosphatidylglycerol and cardiolipin mixtures. Cardiolipin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 74 publications
2
10
0
Order By: Relevance
“…A recent molecular dynamics study showed that there is an increase in the free-energy cost of forming pores in saturated membranes (DMPG) in the liquid-crystalline state when the membranes contain CL. This increase in energy cost was attributed to the negative curvature of the molecule which augmented the curvature energy cost of pore formation by participating directly in the pore structure [ 35 ]. The inhibition of antimicrobial peptides because of the negative curvature of CL has also been discussed extensively elsewhere [ 36 , 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…A recent molecular dynamics study showed that there is an increase in the free-energy cost of forming pores in saturated membranes (DMPG) in the liquid-crystalline state when the membranes contain CL. This increase in energy cost was attributed to the negative curvature of the molecule which augmented the curvature energy cost of pore formation by participating directly in the pore structure [ 35 ]. The inhibition of antimicrobial peptides because of the negative curvature of CL has also been discussed extensively elsewhere [ 36 , 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Real bacterial membranes have a highly variable composition, depending on species and environmental conditions ( 49 ) and realistic modeling of a specific membrane is beyond the scope of the current study. Future work could consider other important classes of lipid, such as cardiolipins ( 17 ), which have been implicated in resistance to AMP's ( 50 ), or models of asymmetric membranes ( 51 ).…”
Section: Discussionmentioning
confidence: 99%
“…The different percentage content of cardiolipin in membrane may affect the effectivness of many permeabilizers such as antimicrobial peptides. 45,46 Natural and synthetic permeabilizers of outer bacteria membrane Therefore, when searching for new alternatives to antibiotics, the permeabilization of the bacterial OM has to be taken into account. There has been an increase in papers describing antimicrobial properties of different permeabilizing agents, including natural (AMPs, antimicrobial proteins, e.g., Lysozyme or Gasdermin D) and synthetic agents, such as nanomaterials (including dendritic NPs).…”
Section: Biomaterials Sciencementioning
confidence: 99%
“…The different percentage content of cardiolipin in membrane may affect the effectivness of many permeabilizers such as antimicrobial peptides. 45,46…”
Section: Introductionmentioning
confidence: 99%